A multi-scale finite element approach to mechanical performance of polyurethane/CNT nanocomposite foam. (September 2020) - Javid, Mehdi; Biglari, Hasan
Abstract: Manufacturing and testing of polymer nanocomposites reinforced with nanoparticles is not cost effective due to high costs of nanomaterials and nanoparticles dispersion problems, and is very time consuming. Therefore, predicting the mechanical properties of these materials using finite element methods is a suitable solution. Accordingly, in the present study, multi-scale finite element method considering the random distribution of carbon nanotubes (CNT) in polyurethane foam is developed to investigate the mechanical behavior of these foams. Experimentally examinations under uniaxial compressive load and SEM tests are performed on samples of polyurethane foam reinforced with 2 wt% and 4 wt% carbon nanotubes. In order to consider the realistic assumptions, the interface between the nanotubes with the matrix is simulated using the cohesive zone model, whose parameters are obtained by calibrating the finite element model results with the experimental results of the polyurethane/CNT nanocomposite foam. The results show that the multi-scale finite element model developed in this study shows the good agreement with experimental results. Moreover, with this method simulation of the mechanical behavior of polyurethane foam reinforced with carbon nanotubes with real conditions becomes possible. Hence, it is easy to determine the impact of effective parameters on mechanical properties of these materials. Experimental results show that in comparison with pure foam, by adding 2 wt% and 4 wt% carbon nanotubes to polyurethane foam, the compressive strength of foam is enhanced by 49 % and 82 %, respectively.